Upaya Peningkatan Hasil Belajar IPA Materi Cuaca Melalui Media Pembelajaran Flipchart Kelas 1 Sekolah Dasar - Aliyah, Faridatul; Syafi’, Moh. Agus Syairofi (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This study aims to improve students' learning outcomes on the topic of weather in first grade at SD Muhammadiyah through the use of flipchart learning media. Primary education plays a crucial role in developing students' character and abilities, and understanding weather is essential for environmental awareness. However, students often face difficulties in grasping abstract concepts. Therefore, an innovative approach to teaching is necessary. This Classroom Action Research (CAR) was conducted to explore the effectiveness of flipchart media in enhancing students' understanding. The methods used include observation, interviews, and evaluation of learning outcomes. The results show that the use of flipcharts can increase student engagement and facilitate understanding of weather material. In the first cycle, student learning completeness reached 69.23%, while in the second cycle it increased to 88.46%. This study is expected to make a significant contribution to the development of more effective and innovative teaching methods at SD Muhammadiyah and serve as a reference for educators in improving the quality of education. Thus, the application of appropriate learning media can create a more dynamic and interactive learning environment, as well as encourage students to think critically and creatively.